Experimental and Numerical Post‐buckling Analysis of Thin Aluminium Aeronautical Panels under Shear Load. (22nd January 2014) - Cricrì, G.; Perrella, M.; Calì, C.
ABSTRACT In this work, a novel multi‐hinged test fixture, which can apply a pure shear load to thin panels, is presented. The new device has been used to perform several experimental tests on the shear behaviour of aluminium alloy panels. Four different test configurations have been considered: stiffened and not stiffened panels, with and without a central rectangular cut‐out. The specimens, made of Al 6082 T6, are tested under shear load boundary conditions up to buckling and post‐buckling occurrence. Furthermore, finite element analyses have been performed in order to simulate the four panel configurations tests. The new test fixture has shown the capability to buckle a panel attaining very large out‐of‐plane displacements, if compared to the outcomes of a traditional picture frame test fixture, under the same external load. Numerical and experimental results are finally compared, showing a satisfactory agreement.